Ultrathin Sicopion Composite Cation-Exchange Membranes: Characteristics and Electrodialytic Performance following a Conditioning Procedure - Erik Ayala-Bribiesca; Mario Boucher; Laurent Bazinet (International Journal of Chemical Engineering)
The aim of this work was to investigate the properties of Sicopion membranes: an ultrathin (≈20 μm) composite cation-exchange membrane (CEM) made from sulphonated poly(ether-ether-ketone) (SPEEK) containing different levels of sulphonic-functionalized silica particles (SFSPs). Sicopion membranes were conditioned according to the French Normalization Association procedure, consisting in a series of acid and alkaline washes, and their electrodialytic characteristics were compared to an existent commercial food-grade membrane (CMX-SB). Electrical conductivity of Sicopion membranes was higher than that of CMX-SB membranes (9.92 versus 6.98 mS/cm), as well as their water content (34.0 versus 27.6%). As the SFSP level was reduced, the ion-exchange capacity (IEC) of Sicopion membranes increased. Concerning their electrodialytic performances, Sicopion membranes presented a lower demineralization rate than CMX-SB membranes (35.9 versus 45.5%), due to an OH− leakage through the pores created by dislodging the SFSP particles during the conditioning procedure.